PENDAMPINGAN PEMANFAATAN LIMBAH PADAT PRODUK PERIKANAN DI TPI SODOHOA SEBAGAI PUPUK ORGANIK - R Rosmawati; Rita L Bubun; Mochammad - Assiddieq (Jurnal Dedikasi Masyarakat, 2020)
Tempat Pelelangan Ikan Sodohoa is an area with high levels of pollution every day in Kendari. So far there has not been any attempt to control the problems caused by the production of fishery by-products. This case has become a problem point that will be solve in the Community Partnership Program assistance. The aim of the activity is to improve community knowledge and skills through the utilization of fishery by-product into organic fertilizer so as to increase the use and economic value of the by-product. The program began with discussion with partner groups and the local community involved in fish trading activities at the Tempat Pelelangan Ikan Sodohoa through forum group discussion. The methods used in resolving the problems of partner groups are (1) counseling and improving skills in processing of fishery by-product into organic fertilizer, (2) coaching and mentoring, and (3) dissemination to farmer Subur Makmur. The Pabalu Balu partner group has been able to make organic fertilizer with a simple method processing and has been tested on the Subur Makmur partner group. We hope that they can switch to using organic fertilizer from fishery by-product as a substitute for artificial fertilizer that so far they have often used.